2012
DOI: 10.1007/s00345-012-0929-7
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of expanded criteria donor kidneys that were transplanted at other Eurotransplant centers after being rejected by our institution

Abstract: Based on our findings, we propose that acceptance criteria for marginal donor kidneys need to be widened.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…Despite these controversial debates, there is no doubt that kidney transplant centers have to become more and more familiar with the aging of the population, and therefore, the tolerance to accept kidneys coming from sub-optimal donors has to increase. Friedersdorff et al [4] have reported their experience reviewing 110 kidneys that were primarily rejected in their institution and then transplanted at other Eurotransplant centers. The cold ischemia time average was 16 h.…”
mentioning
confidence: 99%
“…Despite these controversial debates, there is no doubt that kidney transplant centers have to become more and more familiar with the aging of the population, and therefore, the tolerance to accept kidneys coming from sub-optimal donors has to increase. Friedersdorff et al [4] have reported their experience reviewing 110 kidneys that were primarily rejected in their institution and then transplanted at other Eurotransplant centers. The cold ischemia time average was 16 h.…”
mentioning
confidence: 99%
“…One year after transplantation creatinine had fallen to 1.6 ± 0.8 mg/dl in patients transplanted elsewhere, which was not significantly different from the best creatinine of the kidneys transplanted in Freiburg (1.6 ± 0.9 mg/dl, NS). The same results could be shown by Friedersdorff et al ., who described that in 31% of patients rejected in Berlin and transplanted elsewhere, creatinine values were below 1.47% and 94% under 2.97 mg/dl .…”
Section: Discussionmentioning
confidence: 99%
“…The decision whether to accept an organ or not is made predominantly by the transplant surgeon on the basis of a risk‐benefit assessment and is also practiced at our center. Individual preferences of patients are currently less respected , although it is regarded as an essential component of patient care to allow patient participation in medical decisions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a recent singlecenter study comparing renal transplantations from 30 living marginal donors (age over 60 years, with hypertension, with renal cysts, with ovarian cysts, with hysteromyoma, with renal calculus, with renal artery stenosis, or with myasthenia gravis) with 58 non-marginal living kidney transplantations reported 3-year graft survival as 96.7% and 100%, respectively [13]. One hundred ten deceased marginal kidney donations rejected by a transplantation center were transplanted to ESRD recipients in other facilities, and positive results with respect to graft and recipient survival (6 and 7 years, respectively) were reported [14]. Barba et al [15], on the other hand, studied 407 renal transplants from deceased donors with respect to longterm graft survival and reported 26% graft failure for kidney transplants from marginal donors versus 10% for standard criteria kidney donations.…”
mentioning
confidence: 93%